Complementation tests between alkaline phosphatase-constitutive mutants (phoS and phoT) of Escherichia coli. - Levitz, R (1981)
Complementation tests between phoS and phoT mutations showed that they belong to the same cistron. Homozygosis of a heterozygotic partial diploid resulted from allelic transfer from the chromosome to the F' episome.